Improvement in the Chromium(VI)-Diphenylcarbazide Determination Using Cloud Point Microextraction; Speciation of Chromium at Low Levels in Water Samples - Begoña A. Mouco-Novegil; Manuel Hernández-Córdoba; Ignacio López-García (Molecules, 2023)
A reliable, rapid, and low-cost procedure for determining very low concentrations of hexavalent chromium (Cr) in water is discussed. The procedure is based in the classical reaction of Cr6+ with diphenylcarbazide. Once this reaction has taken place, sodium dodecylsulfate is added to obtain an ion-pair, and Triton X-114 is incorporated. Next, the heating of the mixture allows two phases that can be separated by centrifugation to be obtained in a cloud point microextraction (CPE) process. The coacervate contains all the Cr6+ originally present in the water sample, so that the measurement by molecular absorption spectrophotometry allows the concentration of the metal to be calculated. No harmful organic solvents are required. The discrimination of hexavalent and trivalent forms is achieved by including an oxidation stage with Ce4+. To take full advantage of the pre-concentration effect inherent to the coacervation process, as well as to minimize reagent consumption and waste generation, a portable mini-spectrophotometer which is compatible with microvolumes of liquid samples is used. The preconcentration factor is 415 and a chromium concentration as low as 0.02 µg L−1 can be detected. The procedure shows a good reproducibility (relative standard deviation close to 3%).